2006
DOI: 10.1038/nature05198
|View full text |Cite
|
Sign up to set email alerts
|

Distinct catalytic and non-catalytic roles of ARGONAUTE4 in RNA-directed DNA methylation

Abstract: DNA methylation has important functions in stable, transcriptional gene silencing, immobilization of transposable elements and genome organization. In Arabidopsis, DNA methylation can be induced by double-stranded RNA through the RNA interference (RNAi) pathway, a response known as RNA-directed DNA methylation. This requires a specialized set of RNAi components, including ARGONAUTE4 (AGO4). Here we show that AGO4 binds to small RNAs including small interfering RNAs (siRNAs) originating from transposable and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
407
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(441 citation statements)
references
References 27 publications
22
407
0
5
Order By: Relevance
“…Although the abundance of hc-siRNAs is drastically altered in the mutant background (Yu et al, 2010), the overall size distribution of hc-siRNAs in hen1 was only moderately more dispersed from the 24-nucleotide peak (see Supplemental Figure 7 online), suggesting a more stringent size constraint on the 24-nucleotide hc-siRNAs than the AGO1-bound miRNAs. This constraint could result from properties of AGO4, the AGO protein that binds most hc-siRNAs and acts in transcriptional silencing (Zilberman et al, 2004;Qi et al, 2006). We also examined tasiRNAs from Arabidopsis and observed that two abundant TAS3 sRNAs are highly truncated and tailed in hen1 mutants, but with different patterns (see Supplemental Data Set 1 online).…”
Section: Sirnas Are Truncated and Uridylated In Hen1 Mutantsmentioning
confidence: 99%
“…Although the abundance of hc-siRNAs is drastically altered in the mutant background (Yu et al, 2010), the overall size distribution of hc-siRNAs in hen1 was only moderately more dispersed from the 24-nucleotide peak (see Supplemental Figure 7 online), suggesting a more stringent size constraint on the 24-nucleotide hc-siRNAs than the AGO1-bound miRNAs. This constraint could result from properties of AGO4, the AGO protein that binds most hc-siRNAs and acts in transcriptional silencing (Zilberman et al, 2004;Qi et al, 2006). We also examined tasiRNAs from Arabidopsis and observed that two abundant TAS3 sRNAs are highly truncated and tailed in hen1 mutants, but with different patterns (see Supplemental Data Set 1 online).…”
Section: Sirnas Are Truncated and Uridylated In Hen1 Mutantsmentioning
confidence: 99%
“…siRNA would then be produced in the normal way by a DCL. A second possible mechanism for amplification of others have also used the association of sRNAs with an AGO protein as a parameter in the classification process (Baumberger and Baulcombe 2005;Qi et al 2005Qi et al , 2006. Epitope-tagged versions of the AGO proteins are immunoprecipitated, and the associated sRNAs are characterized using the high-throughput sequencing technology.…”
Section: Genetics and The High-throughput Sequencing Revolutionmentioning
confidence: 99%
“…They direct both transcriptional and post-transcriptional gene silencing mechanisms to target loci [1][2][3] by sequence homology between the sRNAs and their targets. 3 Gene silencing is involved in several biological processes of plants, including defending the genome from transposable elements (TEs), development, imprinting, environmental responses and stress memory.…”
Section: Introductionmentioning
confidence: 99%
“…20 This leads to establishment in which DOMAINS REARRANGED METHYLTRANSFERASES (DRM) DRM1 and DRM2 are guided to target loci by a complex formed between the 21/22 nt sRNAs and ARGONAUTE family proteins. 2,3,21 DRM1 and DRM2 then methylate cytosines of target loci in non-CG contexts (CHG and CHH, where H is A, T or C). 4,22 Twenty-4 nt sRNAs then act through the RNA polymerase IV (PolIV)-dependent pathway in a self-reinforcing RNA-dependent maintenance phase that includes methylation of CG and non-CG context cytosines.…”
Section: Introductionmentioning
confidence: 99%